2010
DOI: 10.1097/cnq.0b013e3181c8e2d7
|View full text |Cite
|
Sign up to set email alerts
|

How Do Critical Care Nurses Define a “Good Death” in the Intensive Care Unit?

Abstract: The purpose of this qualitative study was to explore and describe the characteristics of a good death as defined by 15 critical care nurses working in the intensive care unit (ICU) at a hospital in a mid-sized urban city. The target population was registered nurses employed in the intensive care unit where the study was conducted. Given the fact that the sample population was a very specific group, a purposive, convenience sample was utilized to explore the personal thoughts and feelings of the nurses who volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Kock (2011) (41) revealed that most of the study nurses agreed that families need emotional support. (44,45) On the other hand nearly half of the UCCNSs had a negative attitude as they disagreed that educating families of dying patients about death and dying is nursing responsibility. This result may be attributed to students' feelings of anxiety and being uncomfortable to talk about death.…”
Section: Discussionmentioning
confidence: 99%
“…Kock (2011) (41) revealed that most of the study nurses agreed that families need emotional support. (44,45) On the other hand nearly half of the UCCNSs had a negative attitude as they disagreed that educating families of dying patients about death and dying is nursing responsibility. This result may be attributed to students' feelings of anxiety and being uncomfortable to talk about death.…”
Section: Discussionmentioning
confidence: 99%
“…More important, a biomedical approach to care and technology cannot replace nurse presence and empowered caring because patient's individuality, subjectivity and dignity [19] is of utmost importance in wholistic care. Nurses are advocates, a voice when their patients cannot speak for themselves, they challenge the status quo when everything seems hopeless, [40,45] even when physicians want to pursue aggressive medical treatment in futile situations. [45] A biomedical model and technology in high acuity areas has the potential to overshadow humanistic caring, making nurses question what is dignified care in high acuity areas.…”
Section: Empowered Caringmentioning
confidence: 99%
“…Nurses are advocates, a voice when their patients cannot speak for themselves, they challenge the status quo when everything seems hopeless, [40,45] even when physicians want to pursue aggressive medical treatment in futile situations. [45] A biomedical model and technology in high acuity areas has the potential to overshadow humanistic caring, making nurses question what is dignified care in high acuity areas. To ensure wholistic care nurses establish communities of practice, collaborative learning environments, and pedagogic strategies that include mindfulness, reflection, and refinement of emotional and spiritual [46] experiences that have the potential to enhance wholistic care.…”
Section: Empowered Caringmentioning
confidence: 99%
See 2 more Smart Citations